Primeros resultados sistemáticos y bioestratigráficos del yacimiento de tetrápodos fósiles de la facies Buntsandstein de La Mora (Plá de la Calma, Barcelona) - Gaete, R.; Galobart, A.; Marzo Carpio, M.; Palomar, J. (Cuadernos de Geología Ibérica, 1996)
The study of the Triassic tetrapods from the La Mora site (Montseny, Barcelona) is allowing to characterize the faunistic content of the Buntsandstein continental facies in the Catalonian Coastal Ranges. The dominant taxon is the Triassic Amphibian genera Parotosuchus (fam. Capitosauridae), while the remains pertaining to other taxa are scarce. One of the characters present in the La Mora Parotosuchus (double anterior palatal vacuity) is contradictory with the systematic classification criteria given by many authors. In spite of the difficulty to ascribe the Parotosuchus to any especific taxa, the great abundance of remains pertaining to this genera allows to establish a bioestratigraphic correlation between the «Areniscas y lutitas del Figaró» unit of Ihe Montseny-Llobregat domain with sorne levels of late Lower Triassic age, located in the Central Europe basins, and particularly in the Russian platform.
Keywords: Lower Triassic; Buntsandstein; Areniscas y hititas del Figaró; Tetrapods; Parotosuchu&amp